Implementing Halal Tourism in Mount Rinjani National Park: An Analysis of Sembalun and Torean Trekking Routes - Nadia Nuril Ferdaus; Reny Wardiningsih (CV. ULIL ALBAB CORP, 2025)
This study examines the implementation of halal tourism within Mount Rinjani National Park, focusing on the Sembalun and Torean trekking routes. Using a descriptive qualitative approach, data were gathered through direct observations and interviews with local residents and tourists. Data analysis was conducted based on the Global Muslim Travel Index (GMTI) 2019 framework, categorizing needs into